Characterization of SnO2 nanowires synthesized from SnO by carbothermal reduction process - Thanasanvorakun S. (2014)
In this paper, single-crystalline SnO2 nanowires have been successfully prepared by a carbothermal reduction process employing SnO as the starting material and CuO as the catalyst. Their morphologies, purity and sizes of the products were characterized by transmission electron microscopy (TEM), selected area electron diffraction, X-ray diffraction, field emission scanning electron microscopy (FESEM) and Raman spectroscopy, respectively. The FESEM images reveal wire-like and rod-shaped nanowires of about 100-800 μm in length and 30-200 nm in the transverse dimensions. The three observed Raman peaks at 474, 634 and 774 cm-1 indicate the typical rutile phase of the SnO2 which is in agreement with the X-ray diffraction results. The influence of some reaction parameters, including the temperature and the reaction duration, on the forming, morphology and particle size of SnO2 crystallize is discussed. © 2007 Elsevier Ltd and Techna Group S.r.l.